Pengembangan Inovasi Teknologi Berbentuk Website Direktori sebagai Upaya Branding Desa Wisata di Jawa Timur - Aji, Gilang Gusti; Huda, Anam Miftahul; Setianingrum, Vinda Maya; Indrajayani, Galuh Gita; Andriyanto, Andriyanto; Napitupulu, Pesta Asni (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2024)
ENGLISHSeveral regions in Indonesia have developed rural tourism as an effort to increase the economic activities of village communities. However, the development of tourism villages still has obstacles. One of them is related with reliable, interesting, and easily accessible sources of information to get a complete description before carrying out tourism activities in the village. Therefore, the research team examined information needs and media habits, or media consumption habits, as the basis for designing the Dolan Deso directory website in the district area of the ex-karesidenan Kediri. The selection of objects was centered on four districts in East Java, namely Blitar, Trenggalek, Kediri, and Tulungagung, which have tourist villages with good management. In addition, these four districts also have cultural roots, natural views, and attractions that are interesting to promote. The development of this directory website is carried out as a means to facilitate tourists in obtaining information as well as reference materials related to the type of information needed, the character of the media that is often used as a reference by the community, and various features needed as a reference to fulfill information related to Tourism Villages. INDONESIABeberapa wilayah di Indonesia telah mengembangkan Desa Wisata sebagai upaya peningkatan aktivitas ekonomi masyarakat desa, diantaranya di wilayah kabupaten eks-karesidenan Kediri. Namun, pengembangan desa wisata masih memiliki beberapa hambatan, salah satunya terkait sumber informasi terpercaya, menarik dan mudah diakses (accessible) untuk mendapatkan deskripsi lengkap sebelum melaksanakan kegiatan wisata ke desa. Oleh karenanya, im peneliti mengkaji kebutuhan informasi dan media habit  atau kebiasaan penggunaan media sebagai dasar untuk perancangan website direktori Dolan Deso di wilayah kabupaten di eks-karesidenan Kediri. Pemilihan objek dipusatkan di 4 kabupaten di Jawa Timur, yakni Blitar, Trenggalek, Kediri dan Tulungagung yang telah memiliki desa wisata dengan manajemen yang baik. Selain itu, keempat kabupaten ini juga telah memiliki akar budaya, pemandangan alam, dan atraksi yang menarik untuk dipromosikan. Pengembangan website direktori ini dilaksanakan sebagai sarana untuk mempermudah wisatawan dalam mendapatkan informasi sekaligus sebagai bahan rujukan terkait jenis informasi yang dibutuhkan, karakter media yang sering dijadikan rujukan oleh masyarakat, dan berbagai fitur yang dibutuhkan sebagai rujukan untuk memenuhi informasi terkait Desa Wisata.